Dekonstruksi Mitos Ilmu Bebas Nilai: Aksiologi Islamisasi Ilmu Al-Attas dalam Akademisi Modern - Muh. Matori Ali Akbar; Ramsiah Tasruddin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This article critically examines the claim of value-free science, which has long been regarded as an unquestionable axiom within Western epistemology. Employing a qualitative-descriptive-analytical library research method, this article argues that the claim of scientific value-neutrality is, in fact, an epistemological myth that conceals an underlying secular-materialist value content. The analytical framework is drawn from the thought of Syed Muhammad Naquib al-Attas on the Islamization of Knowledge, particularly his concept of the corruption of knowledge and his proposed solution through the concepts of adab and ta'dib. The findings show that secularism infiltrates the structure of Western scholarship through three main elements—dualism, anthropocentric humanism, and a worldview that negates the transcendent dimension—rendering the resulting knowledge never truly neutral but rather laden with ideological interests. As an axiological solution, adab is proposed as the principle of placing things in their right places, which is subsequently institutionalized through ta'dib, an educational process that integrates knowledge with values. This article concludes that the Islamization of Knowledge does not entail a rejection of modern science but rather constitutes a process of epistemological de-Westernization that restores knowledge to its true nature as an axiological trust.